Fodor's 2009 Washington, D.C. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive guide to visiting Washington, D.C., that provides information on neighborhoods, museums, shopping, restaurants, entertainment, activities, accommodation, and more; and offers detailed maps and trip planning advice.
Cover title: Washington, D.C., 2009 with Mount Vernon, Alexandria & Annapolis.
Includes index.
Includes pullout map.
Maps on inside covers.
Young Adult
Keywords: Alexandria (Va.) -- Guidebooks; Annapolis (Md.) -- Guidebooks; Mount Vernon (Va.) -- Guidebooks; Washington (D.C.) -- Guidebooks; Alexandria (Va.) -- Guidebooks; Annapolis (Md.) -- Guidebooks; Mount Vernon (Va.) -- Guidebooks; Washington (D.C.) -- Guidebooks